Hepatitis E virus and fulminant hepatitis–a virus or host‐specific pathology?. (28th July 2014) - Smith, Donald B.; Simmonds, Peter
Abstract Background & Aims Fulminant hepatitis is a rare outcome of infection with hepatitis E virus. Several recent reports suggest that virus variation is an important determinant of disease progression. To critically examine the evidence that virus‐specific factors underlie the development of fulminant hepatitis following hepatitis E virus infection. Methods Published sequence information of hepatitis E virus isolates from patients with and without fulminant hepatitis was collected and analysed using statistical tests to identify associations between virus polymorphisms and disease outcome. Results Fulminant hepatitis has been reported following infection with all four hepatitis E virus genotypes that infect humans comprising multiple phylogenetic lineages within genotypes 1, 3 and 4. Analysis of virus sequences from individuals infected by a common source did not detect any common substitutions associated with progression to fulminant hepatitis. Re‐analysis of previously reported associations between virus substitutions and fulminant hepatitis suggests that these were probably the result of sampling biases. Conclusions Host‐specific factors rather than virus genotype, variants or specific substitutions appear to be responsible for the development of fulminant hepatitis.